2012
DOI: 10.1261/rna.030742.111
|View full text |Cite
|
Sign up to set email alerts
|

Hnrpab regulates neural development and neuron cell survival after glutamate stimulation

Abstract: The molecular mechanisms that govern the timing and fate of neural stem-cell differentiation toward the distinct neural lineages of the nervous system are not well defined. The contribution of post-transcriptional regulation of gene expression to neural stem-cell maintenance and differentiation, in particular, remains inadequately characterized. The RNA-binding protein Hnrpab is highly expressed in developing nervous tissue and in neurogenic regions of the adult brain, but its role in neural development and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Analysis of the cytoplasmic fractions showed a much larger variation in the p37 to p42 ratios (Figure 1B). p37 is more abundant than p42 in the cytoplasmic fractions in brain, consistent with a previous study [31], and we observed the same pattern in both ovary and testis (Figure 1B), suggesting a possible common function of CBF-A among these three tissues.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of the cytoplasmic fractions showed a much larger variation in the p37 to p42 ratios (Figure 1B). p37 is more abundant than p42 in the cytoplasmic fractions in brain, consistent with a previous study [31], and we observed the same pattern in both ovary and testis (Figure 1B), suggesting a possible common function of CBF-A among these three tissues.…”
Section: Resultssupporting
confidence: 92%
“…In order to examine whether CBF-A plays a role in the Prm2 mRNA regulation in vivo, we analyzed the Prm2 mRNA and PRM2 expression in the testis of the recently established CBF-A knockout mouse, referred to as Hnrnpab −/− [31]. Using the SAK22 and ICCI antibodies, we confirmed that neither p37 nor p42 are present in the testes of homozygous mice (Figures 7A–B; Figure S5).…”
Section: Resultsmentioning
confidence: 84%
“…However, since both Samba and hnRNP AB have been reported to play a role in neural development, we performed functional assays focused on neural development [11], [17].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were then washed in PBS with 0.1 M glycine (PBSG) for 10 min and then permeabilized and stored in 80% methanol overnight at −20°C. Neuronal cultures were maintained according to the procedure described previously (Sinnamon et al 2012). Briefly, E18 timed pregnant mice were sacrificed using CO 2 in accordance with IACUC protocols.…”
Section: Cell Culturementioning
confidence: 99%